2017
DOI: 10.1590/2317-1782/20172016201
|View full text |Cite
|
Sign up to set email alerts
|

Habilidades auditivas de figura-fundo e fechamento em controladores de tráfego aéreo

Abstract: RESUMO Objetivo Investigar o perfil das habilidades auditivas de fechamento e figura-fundo e fatores relacionados à atenção, comunicação e saúde de controladores de tráfego aéreo (CTA) de aproximação de aeronaves e comparar com os de outros profissionais civis e militares. Método Participaram 60 adultos com limiares audiométricos normais reunidos em dois grupos, pareados por idade e gênero: o grupo estudo formado por 30 profissionais do Controle de Aproximação de aeronaves e o controle, por 30 outros servido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…The purpose of a match case-control study conducted in 2017, in which the case group consisted of military professionals working in the Air Traffic Controllers department and the control group consisted of civilian or military personnel in other departments, was to find suitable predictors of participants that could be grouped together in terms of listening skills, health-related factors, etc. Based on the univariable analysis, burnout was significantly higher in the case group than in the control group, but according to the multivariable analysis, burnout was not a significant predictor of belonging to the groups ( 51 ).…”
Section: Resultsmentioning
confidence: 93%
“…The purpose of a match case-control study conducted in 2017, in which the case group consisted of military professionals working in the Air Traffic Controllers department and the control group consisted of civilian or military personnel in other departments, was to find suitable predictors of participants that could be grouped together in terms of listening skills, health-related factors, etc. Based on the univariable analysis, burnout was significantly higher in the case group than in the control group, but according to the multivariable analysis, burnout was not a significant predictor of belonging to the groups ( 51 ).…”
Section: Resultsmentioning
confidence: 93%
“…A systematic review has revealed that the prevalence of high burnout among soldiers ranges from 0.9% to 40% [ 17 ]. A survey conducted by the Brazilian Air Force found that 86.7% of military professionals serving as Air Traffic Controllers experienced burnout [ 18 ]. In the US Army, it was discovered that 43.4% of soldiers experienced burnout, with this situation worsening with age [ 19 ].…”
Section: Introductionmentioning
confidence: 99%